Analysis of the Diffusion of E-services in Public Sector Using the Decision Tree Method - Ljiljana Kašćelan; Vujica Lazović; Tamara uričković; Rondović Biljana (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
The results of the this study showed that there is a difference in individual and interactive impact of technological, organizational and environmental factors on the diffusion of e-services in the public sector, as well as a difference regarding the factors that independently impact the diffusion of e-services oriented to citizens and those oriented to business. The results of the study also showed that external factors have a predominant impact on the diffusion of e-services oriented to citizens, while, in the case of e-services oriented to business, in addition to external factors, technical factors also have a high impact. For the purposes of this paper, based on the Technology-Organization-Environment framework (TOE), the conceptual model suitable for e-services in the public sector is developed, while the Decision Tree (DT) Method is used for testing the effects of the proposed variables. This study offers valuable inputs both for the government, for creators of national strategies oriented towards the promotion and support of the availability and usage of electronic services in the public sector, which is very important especially for developing countries.
Keywords: C53; C83; O32; O33; 330; ICT diffusion; public e-services; decision tree; TOE framework